Enhancing Education Quality through Teacher Training at Pesantren-Based Junior High Schools - Randi Saputra Amyus; Sohiron; Muhammad Fitriyadi (Institut Agama Islam An-Nawawi Purworejo, 2025)
This study aims to explore the qualitative analysis of teacher training at Pesantren-based Junior High Schools to improve education quality. A qualitative research design was employed, focusing on in-depth interviews and observations to assess the training needs, planning, execution, and evaluation processes. The findings reveal that successful teacher training requires clear objectives, integration of pedagogical skills and religious values, and active participation from stakeholders such as school principals, teachers, and students. Effective training also relies on support from management, appropriate training designs, and diverse teaching methods. However, challenges such as time constraints, lack of facilities, resistance to change, and heavy administrative workloads were identified as obstacles in the implementation. To address these challenges, strategic approaches such as flexible scheduling, a structured evaluation system, and continuous feedback are essential for enhancing the effectiveness of teacher training and improving the overall quality of education in Pesantren-based Junior High Schools. These efforts contribute to the integration of Islamic values in the educational process.